Incidencia del programa de educación y capacitación tributaria en el cumplimiento de los impuestos al valor agregado y renta, de los estudiantes de bachillerato del año 2005 de la Ciudad de Quito - Chiluiza Alvarrasín, Patricia Alexandra (2016)
This present research about the Program Agreement education and training tax imparted to baccalaureate students in 2005, signed between the Internal Revenue Service (SRI, in Spanish) and the Ministry of Education. They seeks to know the perception and reality about the implementation of the program in passive subjects that received the taxation class in subsequent compliance with tax obligations of the Value Added Tax (VAT) and Income Tax from 2011 to 2014. The study and analysis of tax culture programs carried out in Ecuador and other countries, and the results obtained in this investigation allow us to establish criteria and fact judgments that take part in the strengthening of the tax administration especially in the area of Tax Training.